A novel visual servoing approach involving disturbance observer - Lee, JS; Suh, IH; You, BJ; Oh, SR (ICRA '99: IEEE INTERNATIONAL CONFERENCE ON ROBOTICS AND AUTOMATION, VOLS 1-4, PROCEEDINGS, 1999)
To improve the visual servoing performance, several strategies have been proposed by using redundant feature points, by using a point with different height, and by a weighted selection of image features. The performance of these visual servoing methods depends on the configuration between the camera and objects. And redundant feature points require much computational efforts. This paper proposes a visual servoing method based on disturbance observer which compensates the effect of the off-diagonal component of image feature Jacobian to be null. The performance indices such as measurement sensitivity of visual features, sensitivity of the control to noise, and controllability are improved when an image feature Jacobian is given as a block diagonal matrix. The proposed approach is applied to PUMA560 and Samsung FARAMAN 6-axis industrial robot manipulator successfully.